Production of HCl Activated Carbon From Rice Husk Waste - Alwardah, Chairunnisa; Kusuma, Daffa Meifan; Bagastama, Bima; Yuda, Dimas; Wahyuningtyas, Aulia; Aeni, Alfieta Rohmaful (Universitas Tribhuwana Tunggadewi Malang, 2024)
Rice husks are agricultural waste whose utilization is not optimal because the waste is usually only burned. Agricultural waste that is burned will harm the environment. Chemical contents such as cellulose and lignin in rice husks can be used to make active carbon. This research aims to determine the optimum operating conditions for producing carbon, obtain information regarding functional groups and changes in pore surface area on carbon before and after activation, and determine the effect of chemical activator HCl on the carbon produced. Rice husks were carbonized using a furnace at temperatures of 200°C, 250°C, and 300°C for 30, 60, and 120 minutes, followed by chemical activation using HCl for 12, 24, and 36 hours. The research results showed that the carbonization variation of 300°C at 120 minutes was closest to SNI standards: water content of 3.91%, ash content of 14.63%, volatile content of 20.01%, and fixed carbon content of 65.36%. Activation of HCl causes the appearance of carboxylic acids. Chemical activation of HCl for 12 hours resulted in proximate content that was close to the SNI 06-3730-1995 standard and resulted in the husk carbon having a larger pore surface area, namely 141,369 m2/g, compared with the pore surface area of the husk carbon before activation was 118,083 m2/g.